Preparing for export? Medical and nursing student migration intentions post-qualification in South Africa - Gavin George; Candice Reardon (AOSIS, 2013)
Background: The migration of health professionals can have a profound impact on health systems around the globe. The International Organization for Migration's (IOM) Mobility of Health Professionals Research Project (MoHProf) aimed to improve knowledge about the migration of healthcare professionals and understand migration intentions and factors influencing the migration of medical and nursing students. Objectives: The study aimed to determine the proportion of nursing and medical studentswho were intending to emigrate, their attitudes and beliefs about, and the factors influencing their decision to emigrate. Method: This study was conducted at three medical schools and one nursing school in SouthAfrica (n = 298) amongst 260 medical and 38 nursing students. One hundred and twenty-five students were in the final year of their studies and 143 were in their prefinal year. Thirty students did not indicate the year of their studies. Every student present on the day of data collection completed a questionnaire comprising psychometric and survey-based questions. Descriptive and inferential statistics were used to analyse the data. Results: More than a third (37%) of the respondents intended to work or specialise abroad.The majority of medical (58.9%) and nursing (66.6%) students intended to leave SA within five years of completing their medical or nursing studies. The perception of poor working conditions within the health sector, such as long work hours, high patient loads, inadequate resources and occupational hazards, influenced medical students to consider emigrating from South Africa. Conclusion: The high number of medical and nursing students intending to emigrate requires a reassessment of effectiveness of retention strategies for doctors and nurses in the South African healthcare system and actions to improve working conditions in the public healthcare sector.